Survey of Aeromonas hydrophila in three marine fish species from north west Arabian Gulf , Iraq - Al-Maleky, Ghazi M. (University of Thi-Qar Journal of Science, 2013)
This study preformed on 74 samples of marine water fishes (24 of Epinephelus tauvina, 27 of Hilsailisha and 23 of Lethriuns nebulosus). Which collected from North West Arabian Gulf of Basrah. All samples were examined for the presence of Aeromonas hydrophila in muscles. 24 isolates of Aeromonas hydrophila were obtained, 8 (33.3%) from Epinephelus tauvina, 12 (44.4%) from Hilsa ilisha, and 4 (17.39%) from Lethriuns nebulosus. Then all isolates were examined for their ability to hemolytic activity as a virulence factor, the higher percentage of hemolytic activity isolates was found in Epinephelus tauvina.